Learning analytics in higher education: a review of impact scientific literature - Cáceres Reche, Pilar; Rodríguez-García, Antonio-Manuel; Gómez García, Gerardo; Rodríguez Jiménez, Carmen (IJERI: International Journal of Educational Research and Innovation, 2020)
Learning analytics can be defined as a series of techniques for collecting, analyzing and granting processable data generated by students. Their objective is to develop appropriate strategies to improve the learning processes, the performance of the students or that of the institution itself. These types of techniques are especially useful to establish patterns of action that guide and guide the educational process in higher education. Under these premises, the present research aims to analyze the scientific production with the greatest impact on the use of learning analytics in higher education. For this purpose, a quantitative methodology has been followed, based on ten variables: year of publication, periodicals, authors, institutions, countries, type of document, publication format, publication area, language and most cited articles. The results project a research trend that is fully on the rise, especially due to the greater scientific production that has occurred in recent years (2015-2018), highlighting countries such as Australia, the United States and the United Kingdom. The publications, in their great majority, come from conferences and are published in English. The knowledge areas of Computational Sciences and Social Sciences stand out.